The Church's Approach to the Dayak Meratus Tribe’s Culture to Avoid Syncretism - Abraham, Martha Luciana; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
Abstract:Evangelising ethnic groups that have long lived within traditional belief systems requires a contextual approach that is aligned with the culture and values of the communities receiving the Gospel. However, the church often faces challenges in preserving the purity of Christian doctrine when new believers remain strongly connected to ancestral traditions. This phenomenon is also evident among Dayak Meratus Christians in Loksado Village. This study aims to provide a conceptual framework for churches in Loksado and other regions with strong ancestral traditions to develop contextual approaches that help believers avoid syncretism without ignoring valuable cultural heritage. Using a qualitative approach through literature-based research, this study identifies a risk of syncretistic tendencies during the process of embracing Christianity among communities previously shaped by traditional belief systems, which may weaken doctrinal purity and spiritual growth. Therefore, the church must place God and His Word above all human cultural expressions and take concrete measures through contextual biblical teaching, exemplary leadership, holistic pastoral care, and continuous discipleship